Lactobacillus paracasei PS23 improves cognitive deficits via modulating the hippocampal gene expression and the gut microbiota in d-galactose-induced aging mice. Issue 9 (19th April 2022) - Cheng, Li-Hao; Chou, Pin-Yu; Hou, An-Tian; Huang, Chin-Lin; Shiu, Wei-Lin; Wang, Sabrina
Abstract : Probiotic supplements are potential therapeutic agents for age-related cognitive deficits. Abstract : Probiotic supplements are potential therapeutic agents for age-related cognitive deficits. A prior study showed that probiotic Lactobacillus paracasei PS23 (PS23) supplementation delayed age-related cognitive decline in mice. However, the underlying mechanisms remain unclear. This study aimed to investigate the effects of live or heat-killed PS23 (HK-PS23) on cognitive function in d -galactose (d -gal)-induced aging mice and explore the underlying mechanisms. We designed four groups of mice: control, d -gal aging mice, and PS23 supplemented and HK-PS23 supplemented d -gal aging mice. We evaluated memory function and anxiety using Morris water maze and open field tests, respectively. Neural monoamines and activities of superoxide dismutase (SOD) in the hippocampus were evaluated. RNA-seq was used to evaluate hippocampal gene expression profiles in each group, and the composition of the gut microbiota was analyzed. We revealed that PS23 and HK-PS23 supplementation ameliorated d -gal-induced memory deficits and improved motor and anxiety-behaviors in aging mice. In the hippocampus, serotonin levels (5-HT) were increased and the genes involved in neuroplasticity, anti-inflammatory, and antioxidant functions were upregulated in PS23 and HK-PS23 supplemented groups. The gut microbiota showed specific changes. Our results suggest that PS23 and HK-PS23 supplements could ameliorate age-related cognitive decline, possibly by upregulating the genes involved in synaptic plasticity and preventing oxidation and inflammation.